2020
DOI: 10.1038/s41525-020-00152-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of common polygenic risk and gene sets on social skills group training response in autism spectrum disorder

Abstract: Social skills group training (SSGT) is a frequently used behavioral intervention in autism spectrum disorder (ASD), but the effects are moderate and heterogeneous. Here, we analyzed the effect of polygenic risk score (PRS) and common variants in gene sets on the intervention outcome. Participants from the largest randomized clinical trial of SSGT in ASD to date were selected (N = 188, 99 from SSGT, 89 from standard care) to calculate association between the outcomes in the SSGT trial and PRSs for ASD, attentio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…The main problems of multiple distortions under the term "ASD" are also existent. Li et al, [59] show the usage of PRS combined with selected training sets for ASD individuals. This seems to be an interesting approach for PRS and real usage.…”
Section: Discussionmentioning
confidence: 99%
“…The main problems of multiple distortions under the term "ASD" are also existent. Li et al, [59] show the usage of PRS combined with selected training sets for ASD individuals. This seems to be an interesting approach for PRS and real usage.…”
Section: Discussionmentioning
confidence: 99%
“…Social skills group training (SSGT) is a behavioral intervention widely applied in ASD to ameliorate social communication difficulties, with varied responses depending on factors such as age and sex [20]. In addition, our group demonstrated that both rare CNVs and common variant PRS could affect individual intervention outcomes in a randomized controlled trial evaluating the SSGT KONTAKT® [21,22]. Seeking to examine further the role of rare variants on individual outcomes of SSGT and standard care, we performed exome sequencing in the participants and leveraged all level genetic data and clinical information from the KONTAKT® trial [20], as summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to exome sequencing, we used our earlier acquired data on clinically significant copy number variations (CNVs) and common variants polygenic risk score (PRS) for ASD [21,22]. The distribution of PRS for ASD did not differ between individuals with or without VCS/VUS from exome sequencing (P = 0.37, Supplementary Fig 4a…”
Section: Clinically Significant Variants and Phenotype Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations